The Structural Imaging Characteristics and Its Clinical Relevance in Patients with Cerebral Venous Thrombosis—A Retrospective Analysis from One Single Center in China - Zhou, Li-xin; Yao, Ming; Cui, Li-ying; Li, Ming-li; Zhu, Yi-cheng; Ni, Jun; Peng, Bin (Frontiers in Neurology, 2017)
Background: Few studies have investigated structural imaging findings of CVT in China. The structural imaging (head CT and routine brain MRI) can assess any parenchymal lesion, such as hemorrhage and brain edema, secondary to the venous thrombosis and reveal direct signs of occlusion of the venous structure by a clotintraluminal thrombus. Increasing patients can be diagnosed with CVT more rapidly and directly by structural imaging in recent years. The aim of the present study is to determine the structural imaging performance on the diagnosis and outcome of CVT in a large cohort single center of Chinese patients. Methods: We evaluated consecutive patients admitted to our hospital with CVT receiving structural imaging from 1991 to 2015. A neuroradiologist, blinded to clinical data, independently reviewed the structural imaging, including head CT and routine MRI for parenchymal lesions and signs of dural venous sinus thrombosis, as well as the MRV/DSA findings. The Clinical and laboratory data were reviewed and recorded for further analysis. Results: 117 patients were included in this study, 68 (58.1%) were females. Parenchymal lesions were identified in 56.4% (66/117) of the patients on structural imaging, including focal edema in 30.8%, hemorrhage in 19.7% and brain swelling in 4.3% of the patients. Patients with parenchymal lesions presented with more often seizures (P<0.001) and less often headache (p=0.049). Intraluminal thrombus within the sinuses or veins on structural imaging was found in 28.2 %( 33/117) of the patients. Those with intraluminal thrombus were younger (P=0.017), had more acute onset (P=0.015). Patients with intraluminal thrombus on structural imaging had significant more frequent with consciousness disturbance (p=0.005), and more percentage of in-hospital mortality (6.1% vs 2.4%). Patients with both intraluminal thrombus and parenchymal lesions on structural imaging had more acute onset (P=0.01) and present more consciousness disturbance (P=0.007). Conclusion: Intracranial lesions on structural imaging are frequently found in patients with CVT, even though brain swelling might be under-diagnosed in Chinese cohort. Patients with parenchymal lesions intraluminal thrombuson structural imaging, especially with intraluminal thrombus parenchymal lesions simultaneously, tend to have a severe clinical picture and might lead to a devastating or fatal outcome. Structural imaging may